Renewable Methanol as an Agent for the Decarbonization of Maritime Logistic Systems: A Review - Leonel J. R. Nunes (Future Transportation, 2025)
Background: The transition to low-carbon economies has become a global priority, particularly in sectors with high greenhouse gas emissions, such as maritime transport. Renewable fuels, especially methanol, have emerged as promising alternatives to conventional fossil fuels due to their potential to reduce carbon footprints and contribute to sustainable logistics systems. Methods: This study employs a combined qualitative and quantitative approach to assess the impact of renewable fuel production on maritime transport decarbonization. The analysis integrates economic feasibility, energy efficiency, and environmental benefits, providing a comprehensive evaluation of methanol’s role in reducing emissions. Results: Findings indicate that methanol offers significant potential for the decarbonization of maritime transport. Its relatively low production costs and high energy density position it as a viable alternative to traditional fuels. Additionally, the study highlights the substantial reduction in greenhouse gas emissions that methanol adoption could achieve, reinforcing its role in mitigating climate change effects. Conclusions: The study concludes that integrating methanol as a primary fuel in maritime transport can accelerate the sector’s decarbonization. However, successful implementation depends on supportive policy regulations and further research to optimize production and supply chain integration. The findings emphasize the strategic importance of renewable fuels in developing sustainable and resilient logistics systems.